The Effectiveness of Tuina in Relieving Pain, Negative Emotions, and Disability in Knee Osteoarthritis: A Randomized Controlled Trial. Issue 3 (23rd August 2022) - Xu, Hui; Zhao, Chi; Guo, Guangxin; Li, Yulin; A, Xinyu; Qiu, Guowei; Wang, Yuxia; Kang, Bingxin; Xu, Xirui; Xie, Jun; Xiao, Lianbo
Abstract: Objective: To evaluate the effectiveness of Tuina in relieving the pain, negative emotions, and disability of patients with knee osteoarthritis (KOA). Design: Single-center, parallel, randomized controlled trial. Setting: Shanghai Guanghua Integrated Chinese and Western Medicine Hospital, Shanghai, China. Subjects: Adult patients with KOA who were able to speak Chinese and self-report symptoms were eligible. Methods: A total of 104 patients were randomly allocated to receive the 6-week treatment of Tuina (Tuina group) or celecoxib (celecoxib group). Data on pain, negative emotions, and disability were collected at baseline, at week 2, 4, and 6, and follow-up (1 month after the last treatment). The primary outcomes were the pressure pain thresholds. The secondary outcomes were: (1) numerical rating scale at rest and with movement; (2) Hamilton Anxiety Scale; (3) Hamilton Depression Scale; (4) Western Ontario and McMaster Universities Osteoarthritis Index; and (5) clinical effective rate. The adverse events of the trial were evaluated. Results: In total, 99 patients completed the follow-up. Generalized linear mixed models were constructed to analyse the between-group differences. Statistically significant differences were found in the interaction effects ( P  <   .05). In evaluating the group effect, statistical differences were found at week 6 and follow-up ( P  <   .05). Further, all variables showed a time effect ( P  <   .05). A statistical difference in the clinical effective rate was found between the Tuina and celecoxib groups ( P  <   .05). Conclusions: Tuina produced superior effects for pain, negative emotions, and disability over time, as compared to celecoxib in patients with KOA.